Investigation on antimicrobial activities of the plant Swertia chirata Ham. - Sultana, Mst Jesmin; Molla, Md Tamzid Hossain; Alam, MT; Ahmed, Fazle Rabbi Shakil (Journal of Life and Earth Science, 2011)
Biological activities of fresh stem of the plant Swertia chirata Ham. (F. Gentianaceae) extracted in rectified spirit is reported here. The crude rectified spirit extract was fractionated by using standard chromatographic techniques on alumina, which gave six fractions (A, B, C, D, E & F). When subjected to column chromatographic analysis on neutral alumina, fraction D yielded a pure compound tentatively known as AJ-1 that have melting point of 178° C. AJ-1 was screened for its antibacterial activities against 12 pathogenic bacteria, 6 Gram positive and 6 Gram negative, by disc diffusion method at a concentration of 200 μg/disc. The results obtained were compared with those for a standard antibiotic Kanamycin. AJ-1 showed significant activity against Bacillus megaterium (11 mm), Bacillus subtilis (9 mm), Salmonella typhi-A (10 mm), Shigella flexeneriae (10 mm) and Klebsiella sp (11 mm) but a little activity against Staphylococcus aureus. The Minimum Inhibitory Concentrations (MIC) of AJ-1 determined against Bacillus megaterium and Salmonella typhi-A were 128 μg/ml and 128 μg/ml, respectively when tested in a nutrient broth medium. AJ-1 also showed significant activity against the brine shrimp (Artemia salina) nauplii (LC50 value of 9.34 μg/ml), in which the mortality rate increased with the increasing concentration of the compound, suggesting a positive correlation between brine shrimp toxicity and cytotoxicity. Key words: Biological activity; Swertia chirata; Gentianaceae; pathogenic bacteria DOI: 10.3329/jles.v2i2.7494 J. Life Earth Sci., Vol. 2(2) 31-34, 2007